Pre-clinical evaluation of CYP 2D6 dependent drug–drug interactions between primaquine and SSRI/SNRI antidepressants - Jin, Xiannu (Malar J, 2016)
BACKGROUND: The liver-stage anti-malarial activity of primaquine and other 8-aminoquinoline molecules has been linked to bio-activation through CYP 2D6 metabolism. Factors such as CYP 2D6 poor metabolizer status and/or co-administration of drugs that inhibit/interact with CYP 2D6 could alter the pharmacological properties of primaquine. METHODS: In the present study, the inhibitory potential of the selective serotonin reuptake inhibitor (SSRI) and serotonin norepinephrine reuptake inhibitor (SNRI) classes of antidepressants for CYP 2D6-mediated primaquine metabolism was assessed using in vitro drug metabolism and in vivo pharmacological assays. RESULTS: The SSRI/SNRI classes of drug displayed a range of inhibitory activities on CYP 2D6-mediated metabolism of primaquine in vitro (IC(50) 1–94 μM). Fluoxetine and paroxetine were the most potent inhibitors (IC(50) ~1 µM) of CYP 2D6-mediated primaquine metabolism, while desvenlafaxine was the least potent (IC(50) ~94 µM). The most potent CYP 2D6 inhibitor, fluoxetine, was chosen to investigate the potential pharmacological consequences of co-administration with primaquine in vivo. The pharmacokinetics of a CYP 2D6-dependent primaquine metabolite were altered upon co-administration with fluoxetine. Additionally, in a mouse malaria model, co-administration of fluoxetine with primaquine reduced primaquine anti-malarial efficacy. CONCLUSIONS: These results are the first from controlled pre-clinical experiments that indicate that primaquine pharmacological properties can be modulated upon co-incubation/administration with drugs that are known to interact with CYP 2D6. These results highlight the potential for CYP 2D6-mediated drug–drug interactions with primaquine and indicate that the SSRI/SNRI antidepressants could be used as probe molecules to address the primaquine-CYP 2D6 DDI link in clinical studies. Additionally, CYP 2D6-mediated drug–drug interactions can be considered when examining the possible causes of human primaquine therapy failures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-016-1329-z) contains supplementary material, which is available to authorized users.